Technical Efficiency of Nepalese Banking Sector - Hakuduwal, Kishor (NRB Economic Review, 2018)
The paper estimates and assesses the technical efficiency at individual and aggregate levels and categorizes groups of banks at various ranges of efficiency. The commercial and development banks established before 2005 in Nepal has been considered as the population of the study and 20 banks are selected using systematic random sampling. The 180 observations of nine year’s panel data from FY 2006/07 to FY 2014/15 has been used. Stochastic Frontier Approach is used taking three input variables i.e. capital, deposit and human resource cost, and one output variable i.e. loans and advance of sampled banks for analysis. The study found that the average technical efficiency (TE) by nature of banks provide commercial banks as the more efficient than development banks. The joint venture banks are the most efficient than other categories of banks. The average efficiency of banks established inside the Kathmandu valley (Head Office located inside Kathmandu) is lower than the average efficiency of banks established outside the Kathmandu valley (Head Office located outside Kathmandu). Similarly, the banks established after 1995 are found more efficient than the banks established before 1995. The study has important implications for the policymakers to take corrective actions for improving the efficiency of the Nepalese banking sector with respect to human resource policy, deposit collection policy and loan management policy.